Pemberdayaan Guru dan Staff Day Care dalam Pencegahan Penyakit Infeksi Saluran Pernafasan di TPA Shaffana Kecamatan Buah Batu Kota Bandung - Nilapsari, Rika; Purbaningsih, Wida; Suryani, Yani Dewi; Triyani, Yani; Purbaningsih, Purbaningsih (Universitas Nusantara PGRI Kediri, 2024)
Daycare (TPA) provides an alternative for baby and toddler care while parents work by providing standardized educational guidance according to the child's age development with an Islamic approach. However, the positive potential of TPA must be supported by creating a good health environment because toddlers are vulnerable to disease transmission. Based on interviews with school principals and teacher representatives, problems with the transmission of respiratory infection and diarrhea occur quickly in children, especially during the transition period. The purpose of this community service program is to increase the knowledge of teachers and teaching staff about respiratory tract infections which can be highly contagious, as well as how to minimize the occurrence of diseases from outside and increase parenting knowledge in sick children. The implementation method used is counseling, modeling the flow of infection prevention and playing isolation facilities, mentoring teachers and staff regarding implementing infection prevention procedures, and preparing an infection prevention game model. The result of PKM is the dissemination of knowledge to teachers and teaching staff about respiratory tract infections which can be highly contagious, as well as how to minimize the occurrence of diseases from outside, as measured by pre and post-test assessments for each activity.